Pengaruh Bauran Pemasaran terhadap Volume Penjualan (Studi Kasus Yotta Milk di Kota Makassar) - Andi Hikmah Dewi Sriyanti; Mustari Mustari; Syamsu Rijal; Muh. Ihsan Said; Tuti Supatminingsih (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. The purpose of this study was to find out the impact of the marketing mix on the sales volume of Yotta Milk in Makassar. The study used quantitative methods, with data collected through questionnaires distributed to 100 Yotta Milk customers as a representative sample of the population. Multiple linear regression is used as an analysis strategy. Based on the findings of the study, products, prices, and physical evidence all had a beneficial and significant effect on the sales volume of Yotta Milk in Makassar City, both simultaneously and partially. Price variables have greater regression coefficient values than other factors, and are the most influential variables in the study. Keywords: Product, Price, Physical Evidence and Sales Volume